A new design of a test platform for testing multiple partial discharge sources. (January 2018) - Rodrigo Mor, A.; Castro Heredia, L.C.; Harmsen, D.A.; Muñoz, F.A.
Highlights: The measuring circuit in a PD set-up may affect the waveform of recorded PD pulses. Ground inductance of the measuring circuit leads to an oscillatory response. A symmetrical and concentric PD set-up minimize the effect of the measuring circuit. This test platform contributes to repeatability and comparison between measurements. Abstract: Partial discharge (PD) measurements are an effective tool for insulation assessment of high-voltage (HV) equipment widely used in both HV laboratories and in field tests. This paper presents the design of a test platform for electrical detection of partial discharges that contribute to the understanding of the phenomena. The test set-up comprises a collection of electrodes for the production of artificial PD sources frequently found in HV equipment, such as positive corona, negative corona, surface discharges, internal discharges, floating component and free moving particle. The test set-up has been designed in such a way that the gaps and clearances can be adjusted to modify the discharge characteristics, e.g. the discharge inception voltage, amplitude, repetition rate, etc. Besides, the platform has a symmetrical and radial arrangement of the PD sources around the coupling capacitor of the PD measuring systems with contribute to reduce the effect of the measuring circuit on the measurements. Relevant characteristics of the presented design is that the sensing of the PD signals is done by a high frequency current transformer (HFCT) with a wide bandwidth and the acquisition of the signals by a digital oscilloscope. A software tool was designed for the purpose of processing of the digitalized signals which proved to be an excellent workbench for studying the performance of clustering techniques.